THE INFLUENCE OF PRODUCT PRICE AND QUALITY ON PURCHASING DECISIONS WITH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE (STUDY AT PT. MUSTIKA MITRA ABADI ALTIC HOUSEWARE) - Lahagu, Dasar Beriman Hati; Zebua, Elisokhi (UPMI Proceeding Series, 2023)
PT. Mustika Mitra Abadi, a limited company supplier/wholesaler of electrical equipment, is an industry which operates in the field of creating household appliances such as washing machines, blenders, cosmos, spoons, forks and so on. Companies that operate in the field of selling household equipment must be able to increase their market share so that the products PT Mustika Mitra Abadi wants to offer, can be accepted by consumers. After being established, this company will make rapid progress, this can be seen from the market share which continues to expand, the company markets and sells several electrical goods in Medan area and surrounding areas. Competitive prices may discourage switching to competitors. In addition, consumers also consider the value obtained from the product in relation to the price paid. In some cases, consumers may be willing to pay a higher price if they believe the product provides additional value. Product quality also contributes to consumer satisfaction after using the product. High consumer satisfaction can increase consumer loyalty, generate positive reviews and recommendations to others. Previous research is useful for strengthening theories and phenomena that influence variables. This research reviews the factors that influence Product Quality and Service Quality on Purchasing Decisions and Consumer Satisfaction, a Marketing Management Literature Study.